Inside the school. A survey on teaching and evaluation practices and on the training needs of teachers - Susanna Piacenza; Roberto Trinchero (Firenze University Press, 2022)
What are the organizational, didactic, evaluation practices most adopted by teachers? In which of these practices do teachers feel him/herself most effective? In which less? And, consequently, what are the explicit and implicit (ie undeclared) training needs that emerge from this analysis? This article illustrates a survey promoted by Pearson Italia in March 2022 conducted through an online questionnaire filled in by 504 Italian teachers from kindergarten up to upper secondary school. The survey highlights how teachers perceive the importance of acting to improve students' autonomy and cognitive abilities, however, this perception corresponds to an act not always in line with the expectations and requests deriving from scientific research about teacher effectiveness.   Dentro la scuola. Un'indagine sulle pratiche didattiche e valutative e sui bisogni formativi degli insegnanti. Quali sono le pratiche organizzative, didattiche, valutative, maggiormente adottate dagli insegnanti? In quali di queste pratiche gli insegnanti si sentono più efficaci? In quali meno? E, di riflesso, quali sono quindi i bisogni formativi espliciti e impliciti (ossia non dichiarati) che emergono da questa analisi? Il presente articolo illustra un'indagine promossa da Pearson Italia nel mese di marzo 2022 condotta mediante un questionario online compilato da 504 insegnanti italiani dalla scuola dell'infanzia fino alla secondaria di secondo grado. L'indagine fa emergere come gli insegnanti percepiscano l'importanza dell'agire per migliorare le capacità cognitive e l'autonomia degli studenti, tuttavia, a questa percezione corrisponde un agito non sempre in linea con le aspettative e con le istanze derivanti dalla ricerca scientifica in tema di efficacia dell'insegnamento.